Energy Generation From Footsteps Using Piezoelectric Sensors - Somashekhar, G.C; Reddy K.H, Anu; Mariam Biju, Bini; Prateeka, L (International Journal of Computer Sciences and Engineering, 2021)
Human race requires energy at very rapid rate for their living and wellbeing from the time of their arrival on this planet, because of this reason power resources have been worn out and enervated. One of the sectors that have gained much interest is devices that are able to convert ambient energy into electrical energy. This paper presents an experimental model for harvesting kinetic energy of footsteps using Piezoelectric. Piezoelectric materials are promising for energy harvesting from the force generated by human footsteps, into a useful form of electrical energy. Installing piezoelectric tile (Piezotile), we can achieve the little amount of power, a single piezotile, which has the capability to produce a maximum of 5-8 volts, eventually installing numerous piezotile, will provide us with much voltage, and application of additional current source we can generate more amount of power . Piezotile is one kind of piezoelectric transducer which transforms foot stress into electric energy. From the stored energy in the battery, the power is supplied to Radio-frequency identification (RFID) as it uses electromagnetic field to automatically identify and track tags attached to objects. And hence only authorized person with tag can login to RFID and use the energy for various applications.